Corrosion protection properties of polypyrrole coatings formed onto 316 L SS from a solution containing molybdate and salicylate - Ramos, Camila (2022)
The electrosynthesis of PPy films onto 316L stainless steel fromnearly neutral and alkaline solutions containing molybdate and salicylate isreported. The corrosion behaviour of the coatings constituted by hollow rectangularmicrotubes was monitored in Ringer solution using open circuit potentialmeasurements, polarization techniques and electrochemical impedance spectroscopy.The polymer formed in a solution of pH 8 was the most efficient interms of corrosion protection. The coating significantly reduced the pitting corrosionof the substrate. The results were interpreted taking into considerationthe polymer electroactivity, the galvanic interaction polypyrrole/substrate andthe nature of dopants. Silver species were effectively immobilized onto the hollowrectangular-sectioned microtubes of PPy. The modified coatings demonstratedthat they have a good bactericidal activity against Escherichia coli andthey were also able to protect the substrate against corrosion in Ringer solution.